Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

My attempt: $\eqalign{ & \int {{{{x^2} + x + 2} \over {3 - 2x - {x^2}}}} dx \cr & {{ - 1( - {x^2} - 2x + 3) - 2x + 3 + x + 2} \over {3 - 2x - {x^2}}} \cr & = - 1 + {{ - x + 5} \over { - {x^2} - 2x + 3}} \cr & = - 1 + {{5 - x} \over { - {x^2} - 2x + 3}} \cr & = - 1 + {{x - 5} \over {{x^2} + 2x - 3}} \cr} $

I think i've messed up somewhere here, when i've tried to manipulate the minus signs. Carrying on:

Finding ${{x - 5} \over {{x^2} + 2x - 3}}$ as a partial fraction:

$\eqalign{ & {{x - 5} \over {{x^2} + 2x - 3}} \equiv {A \over {(x + 3)}} + {B \over {(x - 1)}} \cr & x - 5 = A(x - 1) + B(x + 3) \cr & x = 1: \cr & - 4 = 4B \cr & B = - 1 \cr & x = - 3: \cr & - 8 = - 4A \cr & A = 2 \cr & so: \cr & {{{x^2} + x + 2} \over {3 - 2x - {x^2}}} \equiv - 1 + {2 \over {(x + 3)}} - {1 \over {(x - 1)}} \cr & \int { - 1 + {2 \over {(x + 3)}} - {1 \over {(x - 1)}}dx} \cr & = - x + \ln |{(x + 3)^2}| - \ln |(x - 1)| + C \cr & = - x + \ln \left( {\left|{{{{(x + 3)}^2}} \over {(x - 1)}}\right|} \right) + C \cr} $

However this is the wrong answer, the right answer is:

$$\int {f(x)dx} = - x + \ln \left( {\left|{{{{(3 + x)}^2}} \over {(1 - x)}}\right|} \right) + C$$

Thank you for your help in advance.

share|improve this question
3  
Note that with the absolute values, you actually have the right answer: $\lvert x-1\rvert = \lvert 1 - x\rvert$. –  Thomas May 7 '13 at 20:00
    
I second the comment made by @Thomas. Your answer and the one given are the same. –  Suugaku May 7 '13 at 20:04
    
@Assad: You did everything beautifully. All they did was to distribute the negative in the term as $\frac{1}{1-x}$ before integrating. As mentioned by Thomas, this is the same. –  Amzoti May 7 '13 at 20:09
    
Thank you everyone! –  Assad May 7 '13 at 21:00

1 Answer 1

up vote 2 down vote accepted

No worries!

$$- x + \ln \left( {\left|{{{{(x + 3)}^2}} \over {(x - 1)}}\right|} \right) + C = - x + \ln \left( {\left|{{{{(3 + x)}^2}} \over {-(1 - x)}}\right|} \right) + C = - x + \ln \left( {\left|{{{{(3 + x)}^2}} \over {(1 - x)}}\right|} \right) + C = $$

share|improve this answer
    
Yep, looks good to me! :-) +1 –  Amzoti May 8 '13 at 0:32

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.